THE ROLE OF BRAND IMAGE IN MEDIATED AMENITIES IN INCREASING TOURIST SATISFACTION - Pantun Harianja; Fuji Rahmadi; Rusiadi Rusiadi; Ade Novalina; Bhaktiar Efendi; Lia Nazliaan Nasution; Suhendi Suhendi; Diwayana Putri Nasution (Universitas Kristen Indonesia Toraja, 2022)
Destination study that is for the role of brand image in mediate amenity to satisfaction tourists in Bukit Lawang . Method analysis by year first in study this use approach SEM (Structural Equation Modelling) . Research results show that 1) By straight a minute have influence positive and significant to brand image on Bukit Lawang . 2) In straight a minute have influence positive and significant to tourist satisfaction at Bukit Lawang . 3) In no direct brand image has role significant in mediate a minute to tourist satisfaction at Bukit Lawang .